Smoke Exposure at Home to the Incidence of Pneumonia in Children Under 5 Years Old (Indian Journal of Forensic Medicine & Toxicology, 2020)
Increased levels of pollutants in the room, apart from the penetration of outdoor pollutants, can also comefrom indoor pollutant sources such as cigarette smoke, smoke from using firewood, and the use of mosquitocoils. Pneumonia is the ultimate overlooked child killer (major “forgotten killer of children”). In KlatenDistrict, pneumonia cases in the last 3 years have increased, 1,068, 1,244, and 1,705. This study was todetermine the relationship between the incidence of pneumonia and exposure to smoke at home in childrenunder 5 years of age in Klaten Regency, Central Java Province. This type of research is observational analyticwith case-control studies. The total sample of 278 (139 cases and 139 controls) children under 5 years ofage resided in Klaten Regency and were recorded as pneumonia cases in the public health care registerin 2012 that met the inclusion and exclusion criteria. The research instrument consisted of a structuredquestionnaire. The results of data analysis showed that the relationship with the incidence of pneumonia inchildren under five was the variable exposure to cigarette smoke (OR=2,053; p=0,017 and 95% CI=1,137-3,705) and exposure to kitchen smoke (OR=2,664; p=0,003 and 95% CI=1,4002-5,0680). Factors associatedwith the incidence of pneumonia in children under 5 years of age in Klaten Regency, Central Java Provinceare exposure to cigarette smoke and exposure to kitchen smoke.